Effectiveness of The Use of Chamomile Aromatherapy on Reducing Stress Levels in Pregnant Women - Yosef Andrian Beo; Yohanes Jakri; Yohana Hepilita; Yuliana Suryati (Malahayati Nursing Journal, 2024)
ABSTRACT Pregnancy is often accompanied by increased stress levels due to physiological and psychological changes, which can negatively impact both maternal and fetal health. Natural and non-invasive methods to alleviate stress during pregnancy are increasingly sought after, with chamomile aromatherapy being a promising option due to its known calming properties. This study aims to evaluate the effectiveness of chamomile aromatherapy in reducing stress levels among pregnant women. Quantitative research, Quasi experiment with a one group pre-post test design. The number of samples used in this research was 30 people using accidental sampling. The research instrument used to measure the stress level of pregnant women is the Perceived Stress Scale (PSS-10). The results of the paired t-test statistical test obtained a p-value of 0.01 ( α 0.05), meaning that there was effectiveness of giving chamomile aromatherapy in reducing stress levels in pregnant women at UPTD Puskesmas Lao. Chamomile aromatherapy is a safe, effective, and accessible method for managing stress in pregnant women, potentially enhancing overall prenatal health and well-being. This study supports the integration of chamomile aromatherapy into prenatal care practices. Keywords : Chamomile Aromatherapy, Stress Reduction, Pregnancy